Examining the Impact of Mediating Innovation Capability and Competitive Advantage on SME Performance - M. Trihudiyatmanto; Bahtiar Efendi; Abiodun Babatunde Onamusi (Journal of Management and Entrepreneurship Research, 2026)
Objective: This study examines how Innovation in Human Resource Practices (InHR) and Transformational Leadership (TL) shape Innovation Capability (IC) and Competitive Advantage (CA), and how these, in turn, affect SMEs performance. Research Design & Methods: The study population consisted of 250 small and medium enterprises (SMEs). Using survey data from SMEs in Kedu Regency/City, Central Java (valid respondents = 200), the authors employed SEM (AMOS). Findings: Empirical results show that human resource practices have a significant positive effect on innovation capability, transformational leadership also shows a significant positive impact on competitive advantage, innovation capability shows a significant positive influence on competitive advantage, innovation capability has a significant positive influence on SMEs performance and transformational leadership has a significant positive effect on competitive advantage, with the model explaining approximately 63.2% of the variance in SMEs performance. Implications & Recommendations: This study provides implications for governments and entrepreneurs in finding appropriate ways to build transformational leadership and innovation in HR practices through the application of innovation capability and competitive advantage. Contribution & Value Added: This research model contributes to deepening understanding in the fields of InHR, TL, IC, and CA on SME performance. This research model combines InHR, TL, IC, and CA, with a focus on SMEs in Kedu Regency, Central Java Province. From the research results, this study confirms that the significant positive influence of these four variables on SME performance arises through better integration between InHR, TL, IC, CA, and SME performance.